Problem-based Instructional Module: The Impact on High School Students' Scientific Process Skills - Alfiatus Sa'diyah; Harlita Harlita; Chandra Adi Prabowo (Biosfer: Jurnal Pendidikan Biologi, 2026)
This study investigates the teacher's and students' perception of problem-based instructional modules on biology learning and its effect on students' scientific process skills. The stages of development were analysis, design, development, implementation, and evaluation (ADDIE). This was a quasi-experimental research with samples selected using cluster random sampling. Data were collected through needs analysis questionnaires, response questionnaires, and pretest-posttest of Science Process Skills (SPS). The module was validated by expert judgments. Data analysis used the Rasch model and paired t-test. Results indicate that the module effectively improves students' science process skills. Positive impressions were given by students and teachers regarding the use of the module. Rasch analysis shows the module helps stimulate students’ understanding and involvement. The N-gain test showed increased scores, especially in the communication aspect. Meanwhile, planning experiments scored lowest, indicating challenges in students’ experimental design skills. A significant difference was found in students' SPS before and after treatment, showing that PBL modules support better engagement and learning outcomes. Teachers observed students being more active, collaborative, and responsive in class discussions and problem-solving tasks. Students reported that the contextual problems enhanced their motivation, understanding, and critical thinking. The module also helped create a student-centered learning environment by promoting inquiry and exploration. Therefore, the PBL-based module for the excretory system is suitable, practical, and effective for improving high school students’ science process skills, fostering scientific literacy, and enhancing overall biology learning experiences.